Using thrombocytopenia modeling to investigate the mechanisms underlying platelet depletion induced by pan‐proteasome inhibitors - Floriane Lignet; Andreas D. Becker; Claude Gimmi; Felix Rohdich; Samer El Bawab (Wiley, 2022)
Abstract Pan‐proteasome inhibitors (pPIs) significantly improve outcomes in patients with multiple myeloma; however, their indiscriminate inhibition of multiple proteasome and immunoproteasome subunits causes diverse toxicities, including thrombocytopenia. We investigated the mechanisms underlying the platelet depletion induced by the pPIs bortezomib, carfilzomib, and ixazomib. An established thrombocytopenia model was adapted for each compound (bortezomib, ixazomib, and carfilzomib) to compare the following two pharmacodynamic mechanisms: a reversible inhibition of new progenitor cell formation (the myelosuppression model) and a reversible effect on the function of megakaryocytes to bud new platelets (platelet formation model). Bortezomib, ixazomib, and carfilzomib plasma concentration profiles and platelet counts were extracted from the literature. Pharmacokinetic (PK) and thrombocytopenia models were developed to predict the PK of these drugs and to describe their effects on proliferating cells and platelet budding. The PK models reproduced the exposure of the three compounds at steady state well compared with those reported in the literature. Both the platelet formation and myelosuppression models seemed able to describe the platelet depletion caused by bortezomib, ixazomib, and carfilzomib. Estimated structural parameters in the myelosuppression model were in the range of the values reported in the literature, whereas the mean transit time estimated with the platelet formation model was 3‐fold to 10‐fold higher than the highest reported value. The model of drug‐induced myelosuppression yielded estimates of structural parameters in the range of those previously reported. The platelet formation model captured the temporal variation reported in clinical studies.